DAMPAK GAME ONLINE ROBLOX TERHADAP MOTIVASI BELAJAR SISWA STUDI KASUS DI SD NEGERI SETIA DARMA 04 - Yunauro Prespi Mubaroq; Yohamintin; Suharjuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the impact of the online game Roblox onthe learning motivation of elementary school students. The focus of the study isdirected at changes in learning behavior, consistency of learning enthusiasm, andthe responses of students, teachers, and parents to the habit of playing onlinegames. This study was conducted at SD Negeri Setia Darma 04 using a qualitativeapproach and case study method. Data were obtained through in-depth interviewswith informants consisting of class teachers, parents of students, and fourth gradestudents who actively play Roblox. This study is based on the researchersconcern because of the rampant children playing online games around theresearchers residence. This study aims to determine the impact of the onlinegame Roblox on the learning motivation of students at SD Negeri Setia Darma 04.